C‐Maf enforces cytokine production and promotes memory‐like responses in mouse and human type 2 innate lymphoid cells. (25th April 2022) - Trabanelli, Sara; Ercolano, Giuseppe; Wyss, Tania; Gomez‐Cadena, Alejandra; Falquet, Maryline; Cropp, Daniela; Imbratta, Claire; Leblond, Marine M; Salvestrini, Valentina; Curti, Antonio; Adotevi, Olivier; Jandus, Camilla; et al.
Abstract: Group‐2 innate lymphoid cells (ILC2s), which are involved in type 2 inflammatory diseases such as allergy, can exhibit immunological memory, but the basis of this ILC2 "trained immunity" has remained unclear. Here, we found that stimulation with IL‐33/IL‐25 or exposure to the allergen papain induces the expression of the transcription factor c‐Maf in mouse ILC2s. Chronic papain exposure results in high production of IL‐5 and IL‐13 cytokines and lung eosinophil recruitment, effects that are blocked by c‐Maf deletion in ILCs. Transcriptomic analysis revealed that knockdown of c‐Maf in ILC2s suppresses expression of type 2 cytokine genes, as well as of genes linked to a memory‐like phenotype. Consistently, c‐Maf was found highly expressed in human adult ILC2s but absent in cord blood and required for cytokine production in isolated human ILC2s. Furthermore, c‐Maf‐deficient mouse or human ILC2s failed to exhibit strengthened ("trained") responses upon repeated challenge. Thus, the expression of c‐Maf is indispensable for optimal type 2 cytokine production and proper memory‐like responses in group‐2 innate lymphoid cells. Synopsis: Group‐2 innate lymphoid cells (ILC2s) exhibit "trained immunity". Here, allergen exposure is found to induce the transcription factor c‐Maf for mounting of an optimal type‐2 inflammatory signaling and memory‐like responses in human and mice. Mouse ILC2s lack c‐Maf at steady‐state, but upregulate upon IL‐33/IL‐25 or allergen exposure. Human cord‐blood ILC2s lack c‐Maf, while c‐Maf levels are high in ILC2s in adult blood. Expression of c‐Maf results in a stronger type‐2 cytokine production and supports memory‐like responses. Knock‐down of c‐Maf in mouse ILC2s protects from lung inflammation induced by the allergen papain. Abstract : Trained immunity" in group‐2 innate lymphoid cells involves induction of the transcription factor c‐Maf in response to allergen.